2015
DOI: 10.22500/sodality.v3i3.10638
|View full text |Cite
|
Sign up to set email alerts
|

Pola Adaptasi Ekologi Dan Strategi Nafkah Rumahtangga Di Desa Pangumbahan

Abstract: Desa Pangumbahan berasal dari kata "kumbah" atau cuci, dimana menurut tokoh masyarakat setempat diambil dari sebuah batu tempat mencuci kaki orang suci pada jaman dahulu menurut cerita sunda. Desa pangumbahan merupakan salah satu desa di Kecamatan Ciracap yang merupakan pemekaran dari Desa Gunung Batu dengan luas wilayah ABSTRAKDesa Pangumbahan memiliki dinamika sosial masyarakat dengan adanya kegiatan ekonomi skala makro dalam bentuk konsesi perkebunan kelapa serta alternatif ekonomi baru untuk pengembangan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
6
0
4
Order By: Relevance
“…2019). It showed that the capital accumulation for the livelihood sustainability in each residential area was contextual (Tridakusumah et al, 2015). In the context of community livelihoods in North Halmahera Regency, especially in the research location, it showed that access to natural capital was supported by local traditions or culture known as Hibualamo (Handoko & Mujabuddawat, 2017).…”
Section: Claims and Accessmentioning
confidence: 91%
See 1 more Smart Citation
“…2019). It showed that the capital accumulation for the livelihood sustainability in each residential area was contextual (Tridakusumah et al, 2015). In the context of community livelihoods in North Halmahera Regency, especially in the research location, it showed that access to natural capital was supported by local traditions or culture known as Hibualamo (Handoko & Mujabuddawat, 2017).…”
Section: Claims and Accessmentioning
confidence: 91%
“…Consider the lack of comprehensive explanation of rural and urban community livelihood transformation, especially in the island's coastal and inland areas. Most of the contexts of study in Indonesia are still descriptive, explaining coping and survival strategies of local communities (Mardiyaningsih, Dharmawan, Kolopaking, Firdaus, & Nielsen, 2018;Tridakusumah, Elfina, Mardiyaningsih, Pioke, & Bumulo, 2015;Yulian, Dharmawan, Soetarto, & Pacheco, 2017). This article will discuss the transformation of rural and urban community livelihood based on the characteristics of the island, coastal, and inland areas.…”
Section: Introductionmentioning
confidence: 99%
“…They were found to be migrated from rural to urban areas. Tridakusumah et al (2015) also investigated the household income strategy in Pangumbahan Village. They found that the migration of a family member in a household provided a broader chance of financial security and viewed as a chance to develop another source of income.…”
Section: Farmer Household Income Strategy In Subak Jatiluwihmentioning
confidence: 99%
“…Hal tersebut berkaitan dengan strategi nafkah yang rumah tangga masyarakat lokal. Tridakusumah et al (2015) menyatakan bahwa strategi nafkah adalah segala kegiatan atau keputusan yang diambil anggota rumahtangga untuk bertahan hidup (survival) dan atau membuat hidup lebih baik. Livelihood Assets atau modal nafkah memiliki peran yang penting bagi rumah tangga dan dalam usaha melakukan strategi nafkah, suatu rumah tangga harus mempunyai modal nafkah.…”
Section: Pendahuluan Latar Belakangunclassified